2005
DOI: 10.1002/jcb.20554
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the epidermal growth factor receptor specific transcriptome: Effect of receptor expression level and an activating mutation

Abstract: Overexpression or expression of activating mutations of the epidermal growth factor receptor (EGFR) is common in cancer and correlates with neoplastic progression. The present study employed Affymetrix oligonucleotide arrays to profile genes induced by ligand-activated EGFR with the receptor either moderately expressed or overexpressed at an in-itself transforming level. These changes were compared to those induced by the naturally occurring constitutively active variant EGFRvIII. This study provides novel ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 47 publications
3
54
0
Order By: Relevance
“…The EGFR gene has been found to be expressed at a significantly higher level in glioblastomas. 8,39 The increase in mRNA level caused by amplification is not always proportional to the number of gene copies; 33 and the effects of the gene copy number on expression levels were more relevant for high-level amplifications in a gene-by-gene analysis; results that were also found in breast and prostate cancers. 40,41 In our series, only the cases with dmin amplification, present in more than 10% of the cells, showed an increase of RNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…The EGFR gene has been found to be expressed at a significantly higher level in glioblastomas. 8,39 The increase in mRNA level caused by amplification is not always proportional to the number of gene copies; 33 and the effects of the gene copy number on expression levels were more relevant for high-level amplifications in a gene-by-gene analysis; results that were also found in breast and prostate cancers. 40,41 In our series, only the cases with dmin amplification, present in more than 10% of the cells, showed an increase of RNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have investigated changes in the transcriptome induced by ligand activation of EGFR or the constitutively active mutant EGFRvIII in mouse fibroblast cell lines expressing either wild-type EGFR (NR6wtEGFR) or EGFRvIII (NR6M) using Affymetrix oligonucleotide arrays (9). One of the genes, whose expression was found to be induced by ligandactivated EGFR and by EGFRvIII, encodes the tyrosine kinase receptor EphA2.…”
Section: Activation Of Egfr Increases Epha2 Mrna and Protein Levelsmentioning
confidence: 99%
“…In correlation, Guo et al (47) recently reported that EphA2 has tumor suppressive functions in mammalian skin and suggested that EphA2 overexpression in tumors is the result of a compensatory feedback defensive mechanism against malignant transformation. In addition, Pedersen et al have shown that activated EGFR induces transcription of a panel of genes (IFN-g responsive genes) whose products have known inhibitory effects on EGFR activity and function, indicative of a negative feedback mechanism abrogating or limiting the tumor-promoting effects of overactivated EGFR (9,48). Furthermore, Macrae et al (35) recently showed that RAF activation stimulates EphA2 expression and that ligand-stimulated EphA2 attenuates activation of the mitogen-activated protein kinase pathway thereby forming a negative feedback loop.…”
Section: Epha2 Functions By Modulating Egf-induced Cell Motilitymentioning
confidence: 99%
See 2 more Smart Citations